Structured Deferral: Synchronization via Procrastination. - MCKENNEY, PAUL E. (Communications of the ACM, 2013)
The article discusses synchronization via procrastination as a structured deferral in software design. Topics covered include lazy approaches like reference counting, garbage collection and lazy evaluation, the significant time needed to detect hardware failure, and the usefulness of synchronization via procrastination when interacting with external state. Also mentioned are the key insight behind hazard pointers, the shortcomings inherent in the strengths of hazard pointers, and the read-side disagreements on current state.